2003
DOI: 10.1037/0022-3514.85.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Are 2D:4D finger-length ratios related to sexual orientation? Yes for men, no for women.

Abstract: The ratio of index and ring finger lengths (2D:4D) is thought to be a marker of prenatal androgen exposure. In a sample of over 2,000 participants, men had significantly lower 2D:4D ratios than women (d ϭ .36 and .23 for right and left hands, respectively), and these results were consistent across ethnic groups. Heterosexual men had significantly lower (more male typical) 2D:4D ratios than gay men (d ϭ .32 and .31 for right and left hands, respectively), and these results tended to be consistent across ethnic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
120
5
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(144 citation statements)
references
References 50 publications
14
120
5
5
Order By: Relevance
“…In accordance with previous literature (e.g. Fink et aI., 2004;Lippa, 2003;Manning, 2002;Williams et aI., 2003), 2D:4D was significantly lower for men (M = .956, SD = .025) than for women (M = .975, SD = .027; t(68) = -3.01,p <.005).…”
Section: D:4d and Cooperative Behaviorsupporting
confidence: 79%
“…In accordance with previous literature (e.g. Fink et aI., 2004;Lippa, 2003;Manning, 2002;Williams et aI., 2003), 2D:4D was significantly lower for men (M = .956, SD = .025) than for women (M = .975, SD = .027; t(68) = -3.01,p <.005).…”
Section: D:4d and Cooperative Behaviorsupporting
confidence: 79%
“…It should be noted that accurate calculation of 2D:4D is not dependent on measurement of finger lengths to 0.01 mm as sexual dimorphism in 2D:4D has been shown from measurements made to the nearest mm with a ruler or tape measure. 22 Each finger was measured twice and comparisons between first and second 2D:4D ratios measurements gave an intraclass correlation coefficient of r 1 ¼ 0.89 for the right hand and r 1 ¼ 0.79 for the left. We used repeated measures ANOVA to calculate the ratio (F) between measurement error (the differences between successive measures of 2D:4D) and between-participant differences.…”
Section: Measurementsmentioning
confidence: 99%
“…Unfortunately, these associations with 2D:4D have been dampened by the enormous amount of nonreplication that has been reported among studies investigating similar study populations (e.g. Male and female homosexuality- Lippa, 2003;Robinson and Manning, 2000;Williams et al, 2000; Polycystic ovary syndrome-Bloski et al., 2008;Cattrall et al, 2005; Aggression-Bailey and Hurd, 2005;Hampson et al, 2008).Studies designed to test the notion that prenatal androgens program certain traits and phenotypes require a standardized, validated method of measuring fingers and determining 2D:4D . This is particularly important as effect sizes on 2D:4D are generally only moderate to low (Kemper and Schwerdtfeger, in press).…”
mentioning
confidence: 99%
“…Previous studies in humans have shown low digit ratios (2D:4D) to be associated with a variety of traits including, enhanced visual spatial ability (Burton et al, 2005;van Anders and Hampson, 2005), increased athleticism (Honekopp et al, 2006a), female homosexuality (Brown et al, 2002;Hall and Love, 2003;Kraemer et al, 2006;Williams et al, 2000), decreased susceptibility to coronary artery disease (Fink et al, 2003;Manning and Bundred, 2000), and greater fertility potential in men (Manning et al, 1998) but lower fertility potential in women (Cattrall et al, 2005). By contrast, high 2D:4D were shown to be associated with high verbal fluency (Burton et al, 2005), increased emotional behavior (Williams et al, 2003), lower waist-hip ratios (Fink et al, 2003), male homosexuality (Lippa, 2003) and an increased risk of breast cancer (Manning and Bundred, 2000). Unfortunately, these associations with 2D:4D have been dampened by the enormous amount of nonreplication that has been reported among studies investigating similar study populations (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation